Fibrin and Fibrinolysis in Cancer - Kwaan, Hau C.; Lindholm, Paul F. (Seminars in Thrombosis and Hemostasis, 2019)
In 1878, Billroth discovered that tumor cells invest themselves in a fibrin thrombus, and he hypothesized that fibrin promotes tumor growth and invasion. Since then, many observations have supported this concept, showing that many hemostatic factors including fibrinogen, fibrin, and components of the fibrinolytic system have indeed a complex interaction with cancer growth and metastasis. Fibrin promotes cell migration by providing a matrix for tumor cell migration and by interactions with adhesive molecules and integrins. Fibrin-containing vascular endothelial growth factor promotes angiogenesis. Fibrin interacts with platelets and leukocytes, and promotes their respective carcinogenic properties. Fibrinolytic components exert different effects on tumors. Plasmin activates latent growth factors, and breaks down extracellular matrix (ECM), while urokinase plasminogen activator (uPA) and the uPA receptor (uPAR) form complexes with vitronectin and integrins to promote tumor cells to adhere to the ECM. This complex also binds the epidermal growth factor receptor on the tumor cell membrane, and signals the RAF-MEK-ERK pathway. The complex also binds to the G protein-coupled receptors leading to cell proliferation. Plasminogen activator inhibitor 1 (PAI-1) inhibits apoptosis, and increases tumor cell survival. PAI-1 also enhances cell senescence, leading to production of tumorigenic cytokines by the senescence secretome. The presence of uPA/uPAR and PAI-1 represents a strong biomarker for tumor aggressiveness and poor prognosis. Multiple attempts by blocking various carcinogenic steps have shown tumor-suppressing effects in experimental animals, but human responses are uncertain without clinical trials.
Keywords: fibrin; fibrinolysis; cancer; thrombosis; carcinogenesis; NETs